Mammalian PITPs at the Golgi and ER-Golgi Membrane Contact Sites. (October 2020) - Cockcroft, Shamshad; Lev, Sima
Phosphatidylinositol (PI)-transfer proteins (PITPs) have been long recognized as proteins that modulate phosphoinositide levels in membranes through their intrinsic PI/PC-exchange activity. Recent studies from flies and mammals suggest that certain PITPs bind phosphatidic acid (PA) and possess PI/PA-exchange activity. Phosphoinositides and PA play critical roles in cell signaling and membrane trafficking, and numerous biochemical, genetic and functional studies have shown that PITPs regulate cellular lipid metabolism, various signaling pathways and intracellular membrane transport events. In this mini-review, we discuss the function of mammalian PITPs at the Golgi and ER-Golgi membrane contact sites (MCS) and highlight DAG (Diacylglycerol) as a central hub of PITPs functions. We describe PITPs-associated phospho-signaling network at the ER-Golgi interface, and share our perspective on future studies related to PITPs at MCSs.